PEMBINAAN KONTEKSTUALISASI MEDITASI DALAM ISLAM TAFSIR AL-AZHAR DAN TAFSȊR IBNU KATSȊR DI HIMPUNAN MAHASISWA YAYASAN AL-KAHFI - Kerwanto Kerwanto; Suhendri Suhendri; Jun Firmansyah; Nur Arfiyah Febriani; Maria Ulva (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The issue of meditation continues to grow in the world because meditation is a solution for solving problems in the modern era to calm the mind and soul. Historically meditation originated outside Islam, but in its development it has become the property of all religions. This means that the principles of meditation are still recognized, but its implementation is in accordance with the Shari'a that has been regulated by the Qur'an and the Sunnah of the Prophet. So in Islam there is a sign of harmony between the types of meditation and the worship carried out by Muslims such as prayer, meditation, dhikr, thanksgiving and itikaf. There are findings that meditation in Islam is different from meditation from other beliefs such as Christian, Buddhist and Javanese meditation. Then integrate it with Tafsȋr Ibnu Katsȋr as a classical mufassir and Hamka who is present as a reforming mufassir who contextualizes tafakur in an Indonesian context